2013
DOI: 10.1093/gbe/evt015
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of MicroRNA169 Gene Copies in Genomes of Flowering Plants through Positional Information

Abstract: Expansion and contraction of microRNA (miRNA) families can be studied in sequenced plant genomes through sequence alignments. Here, we focused on miR169 in sorghum because of its implications in drought tolerance and stem-sugar content. We were able to discover many miR169 copies that have escaped standard genome annotation methods. A new miR169 cluster was found on sorghum chromosome 1. This cluster is composed of the previously annotated sbi-MIR169o together with two newly found MIR169 copies, named sbi-MIR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…In the present study pvu-miR166d was predicted to target kinase mRNA, which is in agreement with the reported target kinase for miR166 family in soybean [67]. Calvino and Messing [68] established that miR169 family in Sorghum targets the carboxypeptidase mRNAs. Similarly, in the present study, pvu-miR169b was predicted to target the carboxyl-terminal-processing protease.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study pvu-miR166d was predicted to target kinase mRNA, which is in agreement with the reported target kinase for miR166 family in soybean [67]. Calvino and Messing [68] established that miR169 family in Sorghum targets the carboxypeptidase mRNAs. Similarly, in the present study, pvu-miR169b was predicted to target the carboxyl-terminal-processing protease.…”
Section: Discussionsupporting
confidence: 91%
“…A well-known drought-responsive miRNA, miR169, identified exclusively from control transcriptomes did not appear to accumulate in response to drought (Li et al 2008;Trindade et al 2010;Zhang et al 2011;Calviño and Messing 2013;Potkar et al 2013;Ni et al 2013;Luan et al 2014;Borowski et al 2014). Further evidence supporting the drought-related roles of this miRNA, along with two others (miR1136 and miR1137), was provided by the target analysis, in which these miRNAs were observed to bind stress-related proteins ( Fig.…”
mentioning
confidence: 85%
“…It has been suggested that miR169-dependent NF-YA regulation can be involved in response to stresses in A. thaliana and maize (Leyva-Gonzalez et al 2012;Nelson et al 2007;Pant et al 2009). Its implications in fungal response in wheat (Inal et al 2014), as well as in drought tolerance and stem sugar content, were also described (Calvino and Messing 2013). Additionally, miR169 is involved in nodule development and nutritional balance in legume plants (Simon et al 2009).…”
Section: Target Predictionmentioning
confidence: 99%